Lutzomyia longipalpis behavior and control at an urban visceral leishmaniasis focus in Argentina - Santini, Maria Soledad; Salomón, Oscar Daniel; Acardi, Soraya Alejandra; Sandoval, Enrique Adolfo; Tartaglino, Lilian (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
During the earlier stages of visceral leishmaniasis transmission in Posadas City, Misiones, both the night activity and attraction to humans of Lutzomyia longipalpis were assessed, in order to provide preliminary recommendations. The impact of peridomestic deltamethrin spraying performed by local officials was also evaluated. Although Lu. longipalpis were found in traps located over a dog the entire night, 90% of the females were captured from 20.30h to 1.30h, and only landed on a human when he was at a distance of 1.5 m from the dog. Peridomestic spraying of deltamethrin (25 mg/m²) reduced the sand fly capture up to seven days post-intervention without dispersion in the border of the sprayed areas. These results support the recommendations about time-space focus of the protection measures: first half of the night, in the backyard, with pets and domestic animals kept at least 5 m from humans. The deltamethrin as it was used did not seem very effective in this scenario; neither did the eventual use of bed nets, at least in adults, due to the place/hour of sand fly higher activity. This study strengthens the need for a multidisciplinary approach to develop prevention strategies based both on biological and anthropological studies.